Malignant melanoma of the nasal septum "a rare case" - Ghodrat Mohammadi, M.D.; Rezvan Notash, M.D. (Scientific Journal of Medical Science, 2013)
The nose is an uncommon site for a malignant melanoma, representing 2% to 5% of head and neck malignant melanoma. Nasal malignant melanoma develops from the melanocytes residing in mucous membranes that have migrated during embryologic development from the neural crest to the mucosa of the nose and sinuses. We report two case of the nasal septal malignant melanoma. the first case was 48-years –old woman presented with unilateral blood-stained nasal discharge, right side nasal obstruction, and headache for twelve month. Computed Tomography (CT) Scan showed a large soft tissue mass located in the anterior part of the right nasal cavity extending medially in the septum and laterally into the inferior turbinate. Malignant Melanoma was confirmed histopathologically following surgical resection. The second case was a 57-years-old man presenting with (presented with ) the same compliant. he had homogenous soft tissue mass located in the anterior part of the right nasal cavity extending medially in the septum. After endonasal Endoscopic surgery, pathology showed (Pathologic reports were melanotic malignant melanoma ) malignant melanoma.